The Currents of War : A New History of American-Japanese Relations, 1899-1941 - Pash, Sidney (Book collections on Project MUSE., 2014)
From 1899 until the American entry into World War II, U.S. presidents sought to preserve China's territorial integrity in order to guarantee American businesses access to Chinese markets -- a policy famously known as the ""open door."" Before the Russo-Japanese War in 1904, Americans saw Japan as the open door's champion; but by the end of 1905, Tokyo had replaced St. Petersburg as its greatest threat. For the next thirty-six years, successive U.S. administrations worked to safeguard China and contain Japanese expansion on the mainland. The Currents of War reexamines the relationship.